2011
DOI: 10.1118/1.3583697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MR surface coils on PET quantification

Abstract: Purpose: The goal of this work was to investigate the effects of MRI surface coils on attenuationcorrected PET emission data. The authors studied the cases where either an MRI or a CT scan would be used to provide PET attenuation correction (AC). Combined MR/PET scanners that use the MRI for PET AC (MR-AC) face the challenge of absent surface coils in MR images and thus cannot directly account for attenuation in the coils. Combining MR and PET images could be achieved by transporting the subject on a stereotac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 20 publications
1
81
0
Order By: Relevance
“…With results from this study and previous coil attenuation studies, it is evident that hardware attenuation correction is required for combined PET/MR to reach its potential as an accurate quantitative diagnostic tool (Kartmann et al , 2013; Delso et al , 2010; Eldib et al , 2014; MacDonald et al , 2011; Paulus et al , 2012; Dregely et al , 2014). …”
Section: Discussionmentioning
confidence: 69%
“…With results from this study and previous coil attenuation studies, it is evident that hardware attenuation correction is required for combined PET/MR to reach its potential as an accurate quantitative diagnostic tool (Kartmann et al , 2013; Delso et al , 2010; Eldib et al , 2014; MacDonald et al , 2011; Paulus et al , 2012; Dregely et al , 2014). …”
Section: Discussionmentioning
confidence: 69%
“…Hardware vendors redesigned the hardware components in order to minimize their impact, but their effects are still measurable (26,34), albeit of uncertain impact on diagnostic scans in larger patient cohorts. In the specific case of cardiac imaging, the preliminary data now available point to a good general agreement between PET/CT and PET/MR in FIGURE 1.…”
Section: Technical Requirements For Pet/mr Attenuation Correctionmentioning
confidence: 99%
“…121 Moreover, the bilinear energy mapping of CT to attenuation coefficients at 511 keV for nonbiological materials might not be valid. 116 In this regard, Paulus et al, 122 optimized the bilinear CT energy mapping procedure of hardware PET/MR components through the calibration of CT numbers of these components using transmission scanning and reported a reduction of SUV bias in the NEMA phantom from 3.1% to −0.5%.…”
Section: B5 Emission-based Attenuation/motion Estimationmentioning
confidence: 99%
“…In brain imaging, several studies demonstrated that atlas-based segmentation or registration techniques can properly segment or predict bones. 30,70 Our ranking of patient-specificity of emission-based AC methods for lung and bone LACs is conservative as they are merely based on a few recent 42,116 studies showing the high potential of these methods for the derivation of lung LACs. However, further studies are required to demonstrate the performance of these AC methods for different tracers, cohorts of patients, and TOF resolutions.…”
Section: A Technical Aspects Of Mri-guided Attenuation Correction mentioning
confidence: 99%